2015
DOI: 10.1186/s12889-015-2496-5
|View full text |Cite
|
Sign up to set email alerts
|

Do open youth unemployment and youth programs leave the same mental health scars? - Evidence from a Swedish 27-year cohort study

Abstract: BackgroundRecent findings suggest that the mental health costs of unemployment are related to both short- and long-term mental health scars. The main policy tools for dealing with young people at risk of labor market exclusion are Active Labor Market Policy programs for youths (youth programs). There has been little research on the potential effects of participation in youth programs on mental health and even less on whether participation in such programs alleviates the long-term mental health scarring caused … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 33 publications
1
8
0
1
Order By: Relevance
“…Three studies showed significant effects when controlling for confounders including mental health at baseline: Strandh et al showed that Swedish 18- to 21-year-old NEETs who were actively seeking for work had more internalized mental health problems at age 21 and 43 than employed individuals [43]. Thern et al still found a significant effect of registered unemployment for more than 6 months at age 17 to 24 on mental health at age 34/35 when controlling for mental health at baseline [40].…”
Section: Resultsmentioning
confidence: 99%
“…Three studies showed significant effects when controlling for confounders including mental health at baseline: Strandh et al showed that Swedish 18- to 21-year-old NEETs who were actively seeking for work had more internalized mental health problems at age 21 and 43 than employed individuals [43]. Thern et al still found a significant effect of registered unemployment for more than 6 months at age 17 to 24 on mental health at age 34/35 when controlling for mental health at baseline [40].…”
Section: Resultsmentioning
confidence: 99%
“…From the 108 remaining articles, 64 were removed because they did not meet the eligibility criteria. This left 46 [12, 35-79] in the actual review (see Figure 1). Common reasons for exclusion were lack of pertinence, not meeting the inclusion criteria and treating unemployment as a dependant variable.…”
Section: Resultsmentioning
confidence: 99%
“…It is often argued that well developed welfare states with active labour market policies can buffer the negative effects of a precarious labour market [ 15 ]. In a recent Swedish study, it was found that programs directed at young persons at risk of labour market exclusion led to a positive mental health development later in life, compared to those who experienced unemployment during the same time period [ 16 ].…”
Section: Introductionmentioning
confidence: 99%